Advances in Lipid‐Based Codelivery Systems for Cancer and Inflammatory Diseases. Issue 7 (16th December 2022) - Jogdeo, Chinmay M.; Panja, Sudipta; Kanvinde, Shrey; Kapoor, Ekta; Siddhanta, Kasturi; Oupický, David
Abstract: Combination therapy targeting multiple therapeutic targets is a favorable strategy to achieve better therapeutic outcomes in cancer and inflammatory diseases. Codelivery is a subfield of drug delivery that aims to achieve combined delivery of diverse therapeutic cargoes within the same delivery system, thereby ensuring delivery to the same site and providing an opportunity to tailor the release kinetics as desired. Among the wide range of materials being investigated in the design of codelivery systems, lipids have stood out on account of their low toxicity, biocompatibility, and ease of formulation scale‐up. This review highlights the advances of the last decade in lipid‐based codelivery systems focusing on the codelivery of drug–drug, drug–nucleic acid, nucleic acid–nucleic acid, and protein therapeutic‐based combinations for targeted therapy in cancer and inflammatory diseases. Abstract : This review highlights recent advances in lipid‐based codelivery systems for targeted therapy in cancer and inflammatory diseases with a special emphasis on the design of vectors for codelivery of therapeutic cargo with vastly different physicochemical properties. Different combinations of therapeutic cargo including drug–drug, drug‐nucleic acid, nucleic acid‐nucleic acid, and protein‐based therapeutics delivered using lipid‐based vectors are discussed.